Mantle and crust interaction in post-collisional setting, a case study of lamprophyric-granitic composite dykes of northern Aigoual pluton, French Massif Central - Werle, Mariana (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.